Diagnostic Accuracy of Dual-Layer Spectral CT Using Electron Density Images to Detect Post-Traumatic Prevertebral Hematoma of the Cervical Spine - Sedaghat, Sam; Langguth, Patrick; Larsen, Naomi; Campbell, Graeme; Both, Marcus; Jansen, Olav (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose To investigate the diagnostic value of dual-layer spectral detector computed tomography (SDCT) in detecting posttraumatic prevertebral hematoma of the cervical spine by including electron density images.Methods 38 patients with post-traumatic imaging of the cervical spine were included in this study and received both SDCT and MRI examinations. MRI was set as the reference and combined conventional/electron density (C + ED) images were compared to conventional CT (CCT) images alone.Results A total of 18 prevertebral hematomas were identified. Reader 1 identified 14 of 18 and reader 2 15 of 18 prevertebral hematomas by using C + ED reconstructions. Readers 1 and 2 detected 6 and 9 of 18 hematomas on CCT, respectively. CCT showed a sensitivity of 33–50 % and a specificity of 75–80 %, while for C + ED reconstructed images the sensitivity was 77–83 % and the specificity was 85–90 %. Accuracy increased from 55–66 % to 84 % by using C + ED images. The minimum thickness for detecting hematoma on C + ED images was 3 mm. The sizes of prevertebral hematoma on CCT/C + ED were not significantly under- or overestimated compared to the MRI reference. There was a significant difference between the two readers for measuring hematoma sizes on CCT (p = 0.04). Readers showed an excellent inter-rater reliability (kappa = 0.82) for C + ED images and a moderative inter-rater reliability (kappa = 0.44) for CCT.Conclusion With SDCT, the diagnostic accuracy for detecting post-traumatic prevertebral hematoma is improved by using combined conventional and electron density reconstructions compared to conventional images alone.Key Points: Citation Format
Keywords: dual-layer spectral CT; diagnostic accuracy; prevertebral hematoma; electron density